Programmable Hierarchical Kirigami. (29th November 2019) - An, Ning; Domel, August G.; Zhou, Jinxiong; Rafsanjani, Ahmad; Bertoldi, Katia
Abstract: Kirigami—the Japanese art of cutting paper—has recently inspired the design of highly stretchable and morphable mechanical metamaterials that can be easily realized by embedding an array of cuts into a sheet. This study focuses on thin plastic sheets perforated with a hierarchical pattern of cuts arranged to form an array of hinged squares. It is shown that by tuning the geometric parameters of this hierarchy as well as thickness and material response of the sheets not only a variety of different buckling‐induced 3D deformation patterns can be triggered, but also the stress–strain response of the surface can be effectively programmed. Finally, it is shown that when multiple hierarchical patterns are brought together to create one combined heterogeneous surface, the mechanical response can be further tuned and information can be encrypted into and read out via the applied mechanical deformation. Abstract : The mechanical response of kirigami thin sheets with a hierarchical pattern of cuts arranged to form an array of hinged squares is investigated. The combined experimental and numerical results indicate that by tuning the geometric parameters of this hierarchy not only can a variety of different buckling‐induced 3D deformation patterns be triggered, but also the stress–strain response of the surface can be effectively programmed.